Applying LPIS data to assess loss of agricultural land – experiences from Flanders and Denmark. Issue 1 (2nd January 2019) - Kerselaers, Eva; Levin, Gregor
ABSTRACT: Worldwide, loss of farmland due to transition to other land uses is recognized as a major challenge. Data from the Land Parcel Identification System (LPIS) are potentially useful to assess agricultural land use dynamics as they contain detailed information on agricultural land use. In this paper, we therefore analyse data from two individual studies, one from Flanders and one from Denmark, to explore whether LPIS data are applicable to assess farmland loss. Our results show that in both Flanders and Denmark, around 4.5% of the total registered farmland area in LPIS was lost in a 5-year period (2008–2013 for Flanders and 2011–2016 for Denmark). Complementary land use data and aerial photo interpretation reveal that the majority of lost registered farmland still was in agricultural use after 5 years. Hence, the confirmed loss was only around 0.5% for Flanders and Denmark. We conclude that both Flemish and Danish LPIS data only with some difficulty are able to quantify loss of farmland and therefore question if LPIS data alone are suitable to assess change in farmland area. The major part of farmland leaving the register is most likely related to a general change in agricultural structure.